Carbon dioxide utilisation for production of transport fuels: process and economic analysis. Issue 6 (3rd June 2015) - Dimitriou, Ioanna; García-Gutiérrez, Pelayo; Elder, Rachael H.; Cuéllar-Franca, Rosa M.; Azapagic, Adisa; Allen, Ray W. K.
<x xml:space="preserve">Abstract</x> Utilising CO2 as a feedstock for chemicals and fuels could help mitigate climate change and reduce dependence on fossil fuels.